The Interplay Between Financial Literacy and Financial Well-being: Perspectives of Pre-Service Teachers - Zartaj Jamil; Dr. Farah Deeba (Indus Journal of Social Sciences, 2025)
Financial literacy empowers all individuals to make informed decisions regarding managing their financial matters more effectively which ultimately fosters their financial well-being. However, there is less research regarding revealing the interrelationship of financial literacy and financial well-being especially with reference to students enrolled in teacher education departments who have to join teaching profession in future. The current research investigates interlink of financial literacy with financial wellbeing of pre-service teachers. For this study, data were collected from 219 (49 males and 179 females) pre-service teachers enrolled in teacher education departments of 03 public sector universities in Multan a major city in South Punjab Pakistan. Based on survey approach, two scales such as financial literacy scale and financial being scale which were pilot tested before using for data collection in the new context were administered. For analysis of the collected data, mean scores, standard deviation and Pearson’s r correlation of coefficient statistics were applied. The findings showed that respondents strongly agreed that they accepted the importance of knowledge about finance and its related outcomes and also recognized the positive role of finance education for their own personal well-being. The study showed a strong positive correlation between financial literacy and its three dimensions and financial well-being. These results reflected strong theoretical evidence from Pakistan teacher education context that financial literacy may be included in the curriculum of teacher education system for teachers’ financial well-being. It is further suggested that the results of this study may be tested in other fields of studies.